Effects of PCSK9 Inhibition With Alirocumab on Lipoprotein Metabolism in Healthy Humans. Issue 4 (24th January 2017) - Reyes-Soffer, Gissette; Pavlyha, Marianna; Ngai, Colleen; Thomas, Tiffany; Holleran, Stephen; Ramakrishnan, Rajasekhar; Karmally, Wahida; Nandakumar, Renu; Fontanez, Nelson; Obunike, Joseph; Marcovina, Santica M.; Lichtenstein, Alice H.; et al.
Abstract : Background: Alirocumab, a monoclonal antibody to proprotein convertase subtilisin/kexin type 9 (PCSK9), lowers plasma low-density lipoprotein (LDL) cholesterol and apolipoprotein B100 (apoB). Although studies in mice and cells have identified increased hepatic LDL receptors as the basis for LDL lowering by PCSK9 inhibitors, there have been no human studies characterizing the effects of PCSK9 inhibitors on lipoprotein metabolism. In particular, it is not known whether inhibition of PCSK9 has any effects on very low-density lipoprotein or intermediate-density lipoprotein (IDL) metabolism. Inhibition of PCSK9 also results in reductions of plasma lipoprotein (a) levels. The regulation of plasma Lp(a) levels, including the role of LDL receptors in the clearance of Lp(a), is poorly defined, and no mechanistic studies of the Lp(a) lowering by alirocumab in humans have been published to date. Methods: Eighteen (10 F, 8 mol/L) participants completed a placebo-controlled, 2-period study. They received 2 doses of placebo, 2 weeks apart, followed by 5 doses of 150 mg of alirocumab, 2 weeks apart. At the end of each period, fractional clearance rates (FCRs) and production rates (PRs) of apoB and apo(a) were determined. In 10 participants, postprandial triglycerides and apoB48 levels were measured. Results: Alirocumab reduced ultracentrifugally isolated LDL-C by 55.1%, LDL-apoB by 56.3%, and plasma Lp(a) by 18.7%. The fall in LDL-apoB was caused by an 80.4% increase in LDL-apoB FCR and a 23.9% reduction in LDL-apoB PR. The latter was due to a 46.1% increase in IDL-apoB FCR coupled with a 27.2% decrease in conversion of IDL to LDL. The FCR of apo(a) tended to increase (24.6%) without any change in apo(a) PR. Alirocumab had no effects on FCRs or PRs of very low-density lipoproteins-apoB and very low-density lipoproteins triglycerides or on postprandial plasma triglycerides or apoB48 concentrations. Conclusions: Alirocumab decreased LDL-C and LDL-apoB by increasing IDL- and LDL-apoB FCRs and decreasing LDL-apoB PR. These results are consistent with increases in LDL receptors available to clear IDL and LDL from blood during PCSK9 inhibition. The increase in apo(a) FCR during alirocumab treatment suggests that increased LDL receptors may also play a role in the reduction of plasma Lp(a). Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01959971. Abstract : Supplemental Digital Content is available in the text.